Proceedings of the 5th Nordic Conference on Human-Computer Interaction: Building Bridges 2008
DOI: 10.1145/1463160.1463195
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation methods and cultural differences

Abstract: This paper reviews issues and problems that arise in cross-cultural usability evaluations. It reports two separate empirical studies of a number of well-known techniques with UK, African and Indian users. The studies examine the effectiveness of methods based on think-aloud protocols, including the DUCE method, to elicit users' views. The results from all the studies show that these established Western methods are less effective with users from other cultures. It suggests that the reasons for this are the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Likewise, research by Biru (2008), and Oyugi et al (2008) indicate studies in Europe and North America might only tell little about the practices in developing countries relating to a different context. Besides cultural differences, differences in application requirements, jobs and work environments, attitudes…”
Section: Usability Evaluationmentioning
confidence: 99%
“…Likewise, research by Biru (2008), and Oyugi et al (2008) indicate studies in Europe and North America might only tell little about the practices in developing countries relating to a different context. Besides cultural differences, differences in application requirements, jobs and work environments, attitudes…”
Section: Usability Evaluationmentioning
confidence: 99%
“…Therefore, if software is targeting child users in other countries, the applicability and limitations of current evaluation methods needs to be examined. User experience studies with adults have shown that cultural differences might affect the results, for example, Oyugi, Dunkley, and Smith (2008) found that Kenyan users, when compared to UK users, were much less comfortable with probing questions. It is therefore likely that cultural differences will be evident when using user experience evaluation methods with children.…”
Section: Children As Evaluators Of Technologymentioning
confidence: 99%
“…The‗situated-paradigm' applies to perspectives that respond to the social situation of interactions and the varied non-technological factors that affect design and use (Harrison, 2007).A range of studies illustrate how pairing evaluators with users from different cultural backgrounds influences outcomes (e.g. ; Vatrapu & Perez-Quiñones 2008, Clemmensen & Plocher, 2007Oyugi et al, 2008). In Eastern societies, for example, users' socio-emotional orientations are acutely influenced by the presence of foreign evaluators.…”
Section: Situating the Self In Designmentioning
confidence: 99%